Nano-mechanical properties of diabetic glycogen - Yujun Wan; Yin Yao; Richard D. Tilley; Robert G. Gilbert; Mitchell A. Sullivan (Carbohydrate Polymer Technologies and Applications)
Glycogen, a highly branched glucose polymer, plays a vital role in maintaining blood sugar homeostasis in vivo. Liver glycogen molecules contain small “β particles” bound together into larger composite “α particles”. Previous results showed that the structure of control and diabetic glycogen particles are different. However, changes in their mechanical properties remain unknown. The morphology and stiffness between diabetic and control murine liver glycogen were compared using an atomic force microscope. Morphological parameters of diabetic glycogen, namely particle size, height, and height-to-size ratio, were similar to those of control glycogen. However, the average Derjaguin-Muller-Toporov (DMT) modulus (a measurement of nanoscale stiffness) of diabetic glycogen was significantly higher than that of control glycogen (4.6 ± 0.7 and 3.7 ± 1.2 GPa, respectively). In addition, two types of modulus distribution patterns across glycogen particles were found from both diabetic and control livers, with diabetic glycogen having increases in stiffness towards the top center of particles. The DMT modulus of liver glycogen from control and diabetic mice was reported here for the first time. These findings indicate that diabetes induces a shift from softer to stiffer glycogen particles. This suggests functional and high-level structural differences between healthy and diabetic glycogen, which may have clinical implications, potentially leading to targeted therapies or diagnostic tools for diabetes management.